2016
DOI: 10.5009/gnl15492
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Elastography and Other Magnetic Resonance Imaging Techniques in Chronic Liver Disease: Current Status and Future Directions

Abstract: Recent advances in the noninvasive imaging of chronic liver disease have led to improvements in diagnosis, particularly with magnetic resonance imaging (MRI). A comprehensive evaluation of the liver may be performed with the quantification of the degree of hepatic steatosis, liver iron concentration, and liver fibrosis. In addition, MRI of the liver may be used to identify complications of cirrhosis, including portal hypertension, ascites, and the development of hepatocellular carcinoma. In this review article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 106 publications
0
19
0
Order By: Relevance
“…MRE is an MRI-based method for quantitatively imaging tissue stiffness. Compared with US-based elastography techniques, MRE has advantages of larger volume coverage, higher reliable LS measurement rates [ 42 ]. However, it remains too cumbersome and not standardized enough for widespread use in routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…MRE is an MRI-based method for quantitatively imaging tissue stiffness. Compared with US-based elastography techniques, MRE has advantages of larger volume coverage, higher reliable LS measurement rates [ 42 ]. However, it remains too cumbersome and not standardized enough for widespread use in routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that MRE is a useful noninvasive technique for detecting hepatic fibrosis, and LS values can be used to grade fibrosis (131415). Lee et al (16) reported good repeatability and reproducibility of the LS measurement using MRE.…”
Section: Discussionmentioning
confidence: 99%
“…These technical advantages not only improve the accuracy of fat or iron quantitation but also the reproducibility of the measurements, consistent with a previous study. 35…”
Section: Discussionmentioning
confidence: 99%